Religious Microaggressions: A Case Study of Muslim Americans. Issue 1 (2nd January 2017) - Husain, Altaf; Howard, Stephenie
ABSTRACT: The increasing population of Muslims in America faces challenges not uncommon to other faith and immigrant communities. One particular challenge is Muslim experiences of various forms of discrimination, prejudice, anti-Muslim bigotry, and microaggressions, especially in post-9/11 America. While microaggressions have been discussed in the social sciences literature, religious microaggressions have not been clearly addressed in the social work literature. This article aims to fill this gap in the literature by examining the connections among racial microaggressions, the racialization of religion, and ultimately religious microaggressions. The article concludes by presenting implications for social work policy, practice, and education in the area of religious microaggressions.